Signal Processing with Lapped Transforms - Malvar, Henrique S. (Artech House, 1992)
Here's the first self-contained reference to provide an in-depth discussion of the theory and applications of Lapped Transforms (LTs). The text explains how LTs can lead to a better complexity/performance tradeoff than other transforms or filter banks used in signal processing. It addresses the increased use of LTs, especially in the area of HDTV, and helps you understand why they may well become the standard for high-quality audio coding. The book's appendixes discuss computer programs for LTs and other transforms. These programs are written in ANSI-standard “C”, by far the most portable language. The text is supported by about 330 equations and 100 illustrations. This book is part of Artech House's "In Print Forever" program.